Analysis of quality of service ranking for radio network optimization in Shah Alam / Safuan Zaini - Zaini, Safuan (2013)
Cellular technology is emerging rapidly. Based on the demand of the users, next generation cellular system is being able to provide a variety of applications for user's satisfaction. The Universal Mobile Telecommunication System (UTMS) is a 3rd generation telecommunication system which provides various multimedia applications along with conventional telephony service. The Quality of Service (QoS) is the major concern for real time application such as voice and video telephony. Thus to fulfill the user demand, it is necessary to improve the QoS. The immediate objective of this project is to identify and rank the QoS provided by three ambiguous mobile network operators. Is means real network operator but in order to protect their real identities are replaced by Network Operator A, Network Operator B and Network operator C. This will avoid complication, should you thesis falls in wrong hands. The QoS measured focused on an interactive class of service and based on the end-user perspective. The QoS are measured based on three parameters which are accessibility, retainability and connection or time delay. The data were collected using the Nemo Handy-A installed in a HTC Sensation Z710e smartphone. Drive tests were performed in Shah Alam. The result is analyzed using the average total data for one day. The results indicated that Network Operator C has the best QoS for interactive class of service in Shah Alam followed by Network Operator A and Network Operator B.